REGISTER ARGO MERAPI COMMUNITY (AMC) 14.938 MHz DI DESA ARGOMULYO KECAMATAN CANGKRINGAN SLEMAN YOGYAKARTA - Wahyu Widiastuti; Basuki Basuki (CARAKA, 2016)
The Register of Argo Merapi Community (AMC) 14.938 MHz in the village of Argomulyo Cangkringan Sleman, Yogyakarta. The Thesis of Indonesian Education and Literature Study Program. Faculty of Teachers Training and Education Sarjanawiyata Tamansiswa University Yogyakarta. 2015. This study aims to describe Register Argo Merapi Community (AMC) 14.938 MHz in the village of Argomulyo Cangkringan Sleman Yogyakarta which includes (1) to describe linguistic variation AMC (2) describe the factors that cause the AMC language variation and (3) describe the meaning and typical terms used in the AMC. This research is a qualitative descriptive study. Data were acquired intangible oral sentences spoken AMC. Source of this study was obtained from the use of the language spoken by the AMC. Data obtained using methods refer and methods capable. Techniques to consider methods such as tapping technique, the technique involved skilled free see, the technique involved consider ably, recording techniques and note techniques. Techniques in the form of a conversation methods and techniques of fishing techniques capable semuka. Presentation of the results of this study using formal and informal methods of presentation. Results of this study have concluded that (1) Variation marker linguistic registers in the community AMC (a) phonological variation, (b) morphological variation (c) variations in syntax. The phonological variation found in the AMC involves the removal of the nasal phonemes and their place names beginning with / b / and / d /. Morphological variation of language usage AMC there is a tendency that affixes calendar prefix {happened}. Syntactic variation AMC includes the use incomplete sentences; (2) factors that cause variation in the language of the AMC is (a) the time and place and situation, (b) participants, (c) objectives, (d) the form and content of speech, (e) manner or tone, (f ) different languages, (g) norms or rules interact, and (h) the type or form of delivery; (3) the meaning of the typical terms used in the AMC include: (a) the term natural conditions, (b) the terms of objects, (c) the terms of activities, and (d) the term designation.